The Mycobacterium tuberculosis ESX-3 secretion system interactome - Newton-Foot, Mae (Stellenbosch : University of Stellenbsoch, 2010)
Thesis (MScMedSc (Biomedical Sciences. Human Biology and Human Genetics))--University of Stellenbosch, 2010.